2003
DOI: 10.1161/01.str.0000060029.23872.55
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen Gene Promoter −455 A Allele as a Risk Factor for Lacunar Stroke

Abstract: Background and Purpose-Elevated fibrinogen levels are suggested to increase the risk of myocardial infarction and stroke. Carriers of the A allele of the fibrinogen Ϫ455G/A polymorphism have increased plasma fibrinogen levels. We studied the association of this polymorphism with stroke subtype in the Stroke Aging Memory (SAM) cohort. Methods-The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
4
5

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 60 publications
3
48
4
5
Order By: Relevance
“…55 On a clinical basis, it has been shown that the B␤-455 A/G polymorphism is associated with the development of coronary artery disease in type 2 diabetic subjects, independently of fibrinogen levels. 56 The same polymorphism has been related to the progression of coronary artery disease 57,58 and the development of cerebral infarcts, 59 but not in all studies (Table). 60 …”
Section: Noncoding Polymorphisms Of Fibrinogen Genementioning
confidence: 97%
“…55 On a clinical basis, it has been shown that the B␤-455 A/G polymorphism is associated with the development of coronary artery disease in type 2 diabetic subjects, independently of fibrinogen levels. 56 The same polymorphism has been related to the progression of coronary artery disease 57,58 and the development of cerebral infarcts, 59 but not in all studies (Table). 60 …”
Section: Noncoding Polymorphisms Of Fibrinogen Genementioning
confidence: 97%
“…The severity SEC was shown to be increased with the elevated fibrinogen levels (8). Severe SEC, a marker of atrial stasis, is suggested to associate with thrombus formation and increased systemic embolism risk (19,25). Fibrinogen may be the key element for the development of thrombus and SEC formation.…”
Section: Discussionmentioning
confidence: 99%
“…However, these markers may change instantaneously, and they may also be affected by many other conditions. Recent studies revealed the relationship between beta-fibrinogen 455G/A polymorphism and stroke or myocardial infarction (17)(18)(19). Beta-fibrinogen 455G/A polymorphism was also shown to be associated with the increased erythrocyte aggregation and predisposing the development of stasis (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concentrações plasmáticas elevadas de fibrinogênio foram associadas a maior risco de eventos vasculares como: TVE, doença arterial coronariana e infarto cerebral (Martiskainen et al, 2003;Chen et al, 2008;Bozdemir et al, 2010). Polimorfismos nos genes das cadeias α, β e γ foram associados com o aumento da concentração de fibrinogênio plasmático (De Maat et al, 1998;De Maat, 2001;Manocha et al, 2007;Jacquemin et al, 2008;Siegerink, Rosendaal e Algra, 2009).…”
Section: Polimorfismo No Gene Da Cadeia β Do Fibrinogênio (Fgb -455g>unclassified